Contra commodification of audiences in reporting 212 Brotherhood Reunion in Jakarta / Syaiful Halim and Nuria Astagini - Halim, Syaiful; Astagini, Nuria (Universiti Teknologi MARA, Perak, 2021)
On December 2, 2018 there was an event involving a mass of around five million people in the name of 212 Alumni Brotherhood Reunion. We observed broadcasts conducted by a number of televisions on December 2, 2018 as research instruments. The results showed that some television stations broadcast the reunion event live, while a number of television stations did not do live broadcast of the reunion event. According to the television journalistic perspective, the non-involvement of some television stations in 212 Alumni Brotherhood Reunion in Jakarta on December 2, 2018; the same as post-terror contra by television media. On this situation, the television stations managers neglecting their important role in disseminating information to the whole world; become an intermediary to set the agenda and tell important things for people, also then becomes a channel of interaction for all communication activities. In the end, television media managers became unnecessary to design and produce messages as desired by the public. Meanwhile, according to the commodification perspective, as its nature as a profit search engine, television media is obliged to treat messages as commodities that can please the public, invite advertisers, and extend media business. Profit is the "ideology" behind the production and distribution of media messages. In this context, the audience is treated as a commodity that must be offered to advertisers, by placing it in the segmentation, target, and positioning of a marketing activity, as well as market assets that can absorb advertised products.